Classroom presentation on Mesopotamia - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows children in a classroom delivering a presentation about Mesopotamia. Most of the children are wearing traditional Arab dress. One girl sits at a slide projector. Another child is seated at what appears to be a weaving apparatus. A poster reads: 'Chief crops of Mesopotamia.' The blackboard shows a map of the region and reads: 'Trip to Mesopotamia.' A diorama is on the right.